Body mass index, physical activity, and survival after endometrial cancer diagnosis: Results from the Women’s Health Initiative - Arem, Hannah (2012)
OBJECTIVE: While low physical activity and high body mass index (BMI) have been associated with higher endometrial cancer incidence, no previous studies have evaluated the association between physical activity and survival after endometrial cancer diagnosis, and studies on BMI and survival have not been performed in a prospective cohort. METHODS: We examined pre-diagnosis BMI and moderate- to vigorous-intensity physical activity in relation to overall and disease-specific survival among 983 postmenopausal women who were diagnosed with endometrial cancer in the Women’s Health Initiative Observational Study and Clinical Trials. RESULTS: Over a median 5.2 (max 14.1) years from diagnosis to death or end of follow-up, 163 total deaths were observed, 66 of which were due to endometrial cancer. We observed a higher all-cause mortality hazard ratio (HR)=1.85 (95% CI 1.19–2.88) comparing women with a BMI ≥35 kg/m(2) to women with BMI <25 kg/m(2). For endometrial cancer-specific mortality the HR=2.23 (95% CI 1.09–4.54) comparing extreme BMI categories. To examine histologic subtypes we analyzed type I endometrial tumors separately and found a HR=1.20 (95% CI 1.07–1.35) associated with all-cause mortality for each 5-unit change in BMI. Moderate- to vigorous-intensity physical activity was not associated with all-cause or endometrial cancer-specific mortality. CONCLUSIONS: Pre-diagnosis BMI, but not physical activity, was associated with survival among women with endometrial cancer. Future studies should investigate mechanisms and timing of BMI onset to better understand the burden of disease attributable to BMI.